Optimum processing parameters for wood-bamboo hybrid composite sleepers. (November 2014) - Xiao, Shengling; Lin, Hong; Shi, Sheldon Q; Cai, Liping
The objective of this study was to investigate the optimum processing parameters to manufacture wood-bamboo hybrid composites for railway sleepers. Wood particles and bamboo strips were used as reinforcing materials, and phenol formaldehyde resin was used as matrix. About 108 composite boards with resin contents of 8% to 15.5%, target densities of 0.55 to 1.05 g/cm 3, hot-pressing time of 0.40 to 0.65 min/mm, and press temperatures of 165℃ to 175℃ were fabricated. The effect of manufacturing parameters on the properties of the sleepers was examined. Regression equations were developed to illustrate the relationships between processing parameters and the sleeper properties, i.e. modulus of rapture (MOR), modulus of elasticity (MOE), internal bonding (IB), and thickness swelling (TS). A nonlinear programming model was derived, from which the composite sleeper properties can be estimated. Given the manufacturing conditions (resin content, target composite density, press time, and press temperature), the composite sleeper properties can be estimated. Using the nonlinear programming model, the optimal MOR, MOE, IB, or TS could be obtained under certain practical constraints. When a resin content of 15.5%, target density of 0.8 g/cm 3, hot-pressing time of 0.65 min/mm, and hot-pressing temperature of 170℃ were used, the optimal MOR value of 70.08 MPa was obtained under the conditions that MOE, IB, and TS be greater than the requirements of the standards.